Understanding security issues - Donaldson, Scott E. (Walter De Gruyter Inc., 2019)
With the threats that affect every computer, phone or other device connected to the internet, security has become a responsibility not just for law enforcement authorities or business leaders, but for every individual. Your family, information, property, and business must be protected from cybercriminals in the office, at home, on travel, and in the cloud. Understanding Security Issues provides a solid understanding of the threats, and focuses on useful tips and practices for protecting yourself, all the time, everywhere and anywhere you go. This book discusses security awareness issues and how you can take steps to reduce the risk of becoming a victim: The threats that face every individual and business, all the time. Specific indicators of threats so that you understand when you might be attacked and what to do if they occur. The security mindset and good security practices. Assets that need to be protected at work and at home. Protecting yourself and your business at work. Protecting yourself and your family at home. Protecting yourself and your assets on travel